Identification and Validation of lncRNA-SNHG17 in Lung Adenocarcinoma: A Novel Prognostic and Diagnostic Indicator - Li, Xinyan; Yuan, Yixiao; Pal, Mintu; Jiang, Xiulin (Frontiers in Oncology, 2022)
First, we found that IRRGs were significantly up-regulation in lung cancer and it’s high expression were correlated with poor prognosis, high expression of IRRGs was significantly correlated with the tumor stage and poor prognosis in lung cancer patients. Moreover, KEGG enrichment indicated that these IRRGs are mainly involved in the inflammatory and immune response-related signaling pathway in the progression of NSCLC. We utilized 10 prognostic related genes to construct a prognostic IRRGs model that could predict the overall survival of lung adenocarcinoma (LUAD) patients possess high specificity and accuracy. Our evidence demonstrated that IRRGs expression was significantly correlated with the TMB, MSI, immune-cell infiltration, and diverse cancer-related drug sensitivity. Finally, we identified the upstream regulatory axis of IRRGs in NSCLC, namely lncRNA MIR503HG /SNHG17/miR-330-3p/ regulatory axis. Finally, Knockdown of SNHG17 expression inhibited lung adenocarcinoma (LUAD) cell proliferation and migration. Our findings confirmed that SNHG17 is a novel oncogenic lncRNA and may be a biomarker for the prognosis, diagnosis of LUAD.